PRESERVASI KOLEKSI GREY LITERATURE DALAM KESIAGAAN MENGHADAPI BENCANA DI PERPUSTAKAAN PERGURUAN TINGGI - Haryanto Haryanto (Jurnal IPI (Ikatan Pustakawan Indonesia), 2015)
The purpose of this paper is Knowing Preservation System Implementation grey literature collections in disaster preparedness in the Library, as well as utilization Knowing Collection grey litterature after Preservat 'on held in the collections of disaster preparedness in the Library, This paper used a descriptive approach, The object of his research is the grey littemture preservation activities. Results Implementation ofgray literature collections prese vation system in disaster preparedness in the Library implemented through Digitizing collections, animal exterminc tion destroyer, set binding court decision , restoration page collections, media transfer activity, security librarier , maintaining the cleanliness of the collection and shelves, room temperature settings and user education, wherea ; in the face of disaster preparedness through the stages of preservation activities, preservation, improvement and se rurity.